Bone Plate Removal in Dogs and Cats - Emmerson, T. D.; Muir, P. (Veterinary and Comparative Orthopaedics and Traumatology, 1999)
The medical records and radiographs of 255 consecutive bone plate applications were reviewed. Thirteen percent of the bone plates were removed. Removal of bone plates was most often performed for carpal, tibial, femoral and humeral constructs. Only 9.4% of plates were applied to the tibia and the tarsus, but 27% of plate removals were performed for these skeletal regions.The most common reason for plate removal was construct instability. Factors often associated with unstable constructs included multiple limb injuries, fracture comminution, empty screw holes, engagement of an inadequate number of cortices proximal or distal to the fracture and failure to use cancellous bone autograft. Other reasons for plate removal included infection, soft tissue irritation, and chronic lameness.A series of 255 consecutive bone plate applications were reviewed. Thirteen percent of bone plates were removed. Construct instability was the most common reason for plate removal. Bone plates were also removed because of soft tissue irritation, infection, and chronic lameness. Plate removal was most often performed for tibial and tarsal constructs.
Keywords: Bone plates; removal; construct instability